Tendencies of the library network development in the Siberian and Far Eastern region - E. B. Artemyeva (Библиосфера)
Profound economic transformations beginning in the 1990s had a significant impact on the social sphere development, including the library branch. Delimitation of the state ownership in the Russian Federation (RF) on the federal, RF subjects and municipal properties, entailed the transfer of library management functions to local authorities, contributed to increasing the role of a subjective factor and growing inequality of territories opportunity and library services quality, and consequently, public access to information. Siberia and the Far East being far of the country's administrative center occurred in the most difficult position, that is confirmed by experts determining the level of regions development in terms of «life quality». The article presents the dynamics of the public libraries network in the region as a whole, as well as in separate administrative-territorial formations with different ratings on the level of «life quality», it outlines general trends of the university, academic, scientific-technical and specialized library network development in 1992-2015. It was traced the dependence in library branch transformations on changes in the field of economy, science, education and culture. In 2000s the focus was made on the library activities reconstruction within corporations, centers and associations that promoted forming their compensation qualities in the population information-library services. At the same time, it is actual the joint work of libraries in frameworks of the existing traditional library networks with the local development of the region remote areas, their difficult social-economic situation, weak connectedness of the space, adversely affecting the level of libraries material-technical base and their integration into the information-communication networks and systems.